1983
DOI: 10.1161/01.str.14.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Low protein fish vs low protein animal diet enhances the propensity for stroke in stroke-prone/SHR.

Abstract: SUMMARY Weanling male and female, stroke-prone, spontaneously hypertensive rats (SHR/SP) were fed: 1) regular commercial rat chow, 2) low protein fish diet, 3) low protein fish diet +1% saline, 4) low protein animal diet, and 5) low protein animal diet + 1 % saline. The blood pressure of all of the SHR/SP rose rapidly reaching 240 mmHg at 90 days of age; blood pressure of low protein fish diet +1% saline-fed SHR/SP rose most rapidly, reaching levels ranging from 258 to 300 mmHg. All of these animals developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…110 Interestingly, Tobian et al 111 have shown a dramatic 98% reduction in mortality and complete prevention of Perm.…”
mentioning
confidence: 99%
“…110 Interestingly, Tobian et al 111 have shown a dramatic 98% reduction in mortality and complete prevention of Perm.…”
mentioning
confidence: 99%
“…investigators 4 attributed the higher incidence of stroke produced by the Funahashi-SP diet to the fact that the protein content was not only low but was derived from fish as opposed to animal or plant material. This latter hypothesis, however, has never been confirmed and is further complicated by the fact that elevating the fish, plant, or animal protein levels in the Japanese diet protects against stroke.…”
mentioning
confidence: 99%
“…85 Several studies have demonstrated the importance of diet in the etiology of stroke in SHRSP; they developed strokes only if fed a specific low-protein fish meal diet. 88 Tobian et al 89 observed that increased dietary K + greatly reduced strokes in SHRSP even though there was little or no effect on blood pressure, the implication being that K + has an effect on blood vessels independent of its effect on blood pressure. Tobian et al pointed out that the dietary intake of K + is lowest among blacks in the southeastern US and in certain parts of Japan; areas of Japan where apples (high in K + ) comprise an important dietary staple have a much lower incidence of stroke.…”
mentioning
confidence: 99%